Remotely-sensed products capture the spatial distribution of regional carbon sequestration potential ability: A case study of Hubei Province, China - Zhaolong Li; Lingya Huang; Yuanyong Dian (Ecological Indicators)
Carbon neutrality has emerged as a critical issue both in China and globally, playing a significant role in mitigating climate change, protecting the environment, and enhancing energy security. Understanding the regional distribution of carbon sequestration potential is essential for informing land use and industrial planning strategies. Existing research primarily focuses on the carbon sequestration capacity of forests, while there is an inadequate assessment of the overall regional carbon sequestration potential within the context of land use. To address these research gaps, a Regional Carbon Sequestration Potential Index (RCSPI) was developed to quantitatively evaluate carbon sequestration potential across different regions. This index incorporates multi-source remote sensing variables and environmental factors. This study utilized free and open-source remote sensing data products, including above-ground biomass (AGB), gross primary productivity (GPP), fractional vegetation cover (FVC), and land use classification, to calculate the RCSPI and generate a Pixel Carbon Sequestration Potential Index (PCSPI) map. This approach provides a more comprehensive evaluation of carbon sequestration potential from the pixel scale to regional scale. The performance of the RCSPI was tested using data from 103 county-level regions in Hubei Province. The results showed that the RCSPI showed good ability to facilitate the analysis of distinct carbon sequestration potential patterns, which accruing to the heterogeneity of resource conditions across different regions. Furthermore, we identified three distinct patterns of carbon sequestration potential. Each pattern corresponds to the three indicators of GPP, AGB, and potential carbon sequestration space (F), each exhibiting unique characteristics. Utilizing these patterns, managers can make informed adjustments to regional land management and forestry development policies, which is crucial for achieving carbon neutrality.